Prescription patterns of antibiotics and associated factors among outpatients diagnosed with respiratory tract infections in Jinja city, Uganda, June 2022–May 2023 - Igirikwayo, Zablon K.; Migisha, Richard; Mukaga, Humphreys; Kabakyenga, Jerome (BMC Pulmonary Medicine, 2024)
Background: Most respiratory tract infections (RTIs) are viral and do not require antibiotics, yet their inappropriate prescription is common in low-income settings due to factors like inadequate diagnostic facilities. This misuse contributes to antibiotic resistance. We determined antibiotic prescription patterns and associated factors among outpatients with RTIs in Jinja City, Uganda. Methods: We conducted a retrospective observational study that involved data abstraction of all patient records with a diagnosis of RTIs from the outpatient registers for the period of June 1, 2022, to May 31, 2023. An interviewer administered questionnaire capturing data on prescribing practices and factors influencing antibiotic prescription was administered to drug prescribers in the health facilities where data were abstracted and who had prescribed from June 1, 2022, to May 31, 2023. We used modified Poisson regression analysis to identify factors associated with antibiotic prescription. Results: Out of 1,669 patient records reviewed, the overall antibiotic prescription rate for respiratory tract infections (RTIs) was 79.8%. For specific RTIs, rates were 71.4% for acute bronchitis, 93.3% for acute otitis media, and 74.4% for acute upper respiratory tract infections (URTIs). Factors significantly associated with antibiotic prescription included access to Uganda Clinical Guidelines (Adjusted prevalence ratio [aPR] = 0.61, 95% CI = 0.01–0.91) and Integrated Management of Childhood Illness guidelines (aPR = 0.14, 95% CI = 0.12–0.87, P = 0.002), which reduced the likelihood of prescription. Prescribers without training on antibiotic use were more likely to prescribe antibiotics (aPR = 3.55, 95% CI = 1.92–3.98). Patients with common cold (aPR = 0.06, 95% CI = 0.04–0.20) and cough (aPR = 0.11, 95% CI = 0.09–0.91) were less likely to receive antibiotics compared to those with pneumonia. Conclusion: The study reveals a high rate of inappropriate antibiotic prescription for RTIs, highlighting challenges in adherence to treatment guidelines. This practice not only wastes national resources but also could contribute to the growing threat of antibiotic resistance. Targeted interventions, such as enforcing adherence to prescription guidelines, could improve prescription practices and reduce antibiotic misuse in this low-income setting.
Keywords: Respiratory tract infections; Antibiotic prescriptions; Drug resistance; Prescription drug misuse; Uganda